La mano invisible. Liderazgo, economía política y relaciones sociales en el mundo indígena del sudeste pampeano (1770-1830) - Alemano, María Eugenia (EDITORIAL DE LA UNIVERSIDAD NACIONAL DEL SUR, 2021)
This article analyzes the indigenous mercantile participation and its consequences for leadership and interethnic relations, considering the case of the partialities that inhabited the mountains, dunes and salt marshes of the southeastern pampa between 1770 and 1830. To begin with, we have characterized the socio economic structure of the tolderías of the southeastern pampa in terms of the number of population and the main productive activities linked to  subsistence and trade. Secondly, we sought to glimpse how trade with Buenos Aires energized inter-ethnic relations and the construction of power by the caciques. As various works have shown in recent years, the redistribution of merchandise from the other side of the border was a fundamental political capital for the construction of leadership in the indigenous Arauco-Pampean society. For this reason, the caciques implemented diverse strategies that articulated warlike, diplomatic and commercial practices. We argue that commercial participation was politically motivated, and that influenced the strategies of the caciques in the face of the State advance.